Vacina experimental contra o vírus da diarréia viral bovina (BVDV): avaliação da inocuidade, eficácia e modelo para testes de proteção vacinal - Brum, Mário Celso Sperotto (2002)
This study aimed to evaluate two attenuated strains of bovine viral diarrhea virus (BVDV) as vaccine candidates and to study the effects of inoculation of two Brazilian BVDV type 2 (BVDV-2) isolates in calves. In the first experiment, two isolates of BVDV-2, attenuated by multiple passages in tissue culture associated with ultraviolet irradiation, were evaluated as vaccine candidates. The attenuation of the modified viruses was assessed in calves and in pregnant ewes and their capacity to induce fetal protection was investigated in pregnant ewes. Intramuscular inoculation of the attenuated viruses in four seronegative calves produced only a mild and transient rise in body temperature, followed by the production of high titers of neutralizing antibodies. The viruses were not detected in nasal secretions or in the blood following inoculation. However, intramuscular inoculation of these viruses in four pregnant ewes resulted in transplacental transmission and infection of all fetuses. To assess fetal protection conferred by immunization, pregnant ewes previously immunized with these viruses were challenged by intranasal inoculation with BVDV-1 (SV-126.8, n=6) or BVDV-2 (SV-260, n=5). At the day of challenge (134 days after the second immunization), all ewes had high titers of neutralizing antibodies (256 to >4096) to the vaccine viruses, and variable titers (8 to >4096) to Brazilian BVDV-1 and BVDV-2 field isolates. Fifteen days after challenge, the ewes were euthanized and fetal tissues were examined for infectivity. All fetuses from non-vaccinated, challenged ewes (n=4) were infected. In contrast, none of the fetuses from the immunized dams (n=11) were positive for virus, indicating that the immunological response induced by immunization with the vaccine candidate viruses was capable of preventing fetal infection. These results suggest that it might be possible to achieve by induction of a strong immunological response using a modified live vaccines. In the second experiment, two Brazilian BVDV-2 were inoculated in calves to study virulence and the pathogenesis of viral infection. Previously to vírus inoculation, the calves were immunosupressed with dexametasone. Four 45 to 90-days-old calves (group A) were inoculated with isolate SV-260 (n=2) or LV-96 (n=2), and four 6 to 8-months-old calves (group B) were inoculated with isolate SV-260. Following virus inoculation, group A calves showed anorexia, depression, hyperthermia, signs of respiratory infection and profuse diarrhea, bloody in two cases. The respiratory and digestive signs progressed and the animals died or were euthanized in extremis between days 7 and 12 post-inoculation. Ulcers and erosions in the digestive tract (tongue, n=4; esophagus, n=1; rumen, n=1 and abomasum, n=3), edema of the lung (n=4) and abomasal mucosa (n=3), echimosis and suffusions in the spleen serosa (n=2), rumen, small intestine and ceccum (n=1), heart (n=1) and urinary bladder mucosa (n=1) and intestinal intussuseption (n=1) were the most prominent findings at necropsy. Ulcerations and erosions accompanied by mononuclear cell infiltrates in the digestive tract mucosa and submucosa, and lymphoid depletion in the lymph nodes and Peyer’s patches were frequently observed. Infectious virus was detected in several tissues and organs. Viral antigens were detected by immunohistochemistry mainly in epithelial cells of the digestive tract, in mononuclear cells of the perivascular and peribronchial spaces; in lymph node septae and capsule; and in lymphocytes and mononuclear cells of the spleen and Peyer’s patches. Group B calves showed depression, hyperthermia, moderate signs of respiratory and digestive infection, small ulcerations in the tongue and recovered after a few days. These results demonstrate that the Brazilian BVDV-2 isolates were capable of producing an acute disease in calves upon experimental inoculation, and that the clinical and pathological consequences of the infection were more severe in young calves.